Akurasi Penaksiran Berat Janin menggunakan Metode Johnson pada Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Pare Kabupaten - Sri Widatiningsih; Tulus Puji Hastuti; Murdiyanto Tri Wibowo (Jurnal Riset Kesehatan, 2015)
This  was a cross sectional study intended to test the accuracy of Johnson’s method which will be compared with actual birth weight as a gold standard. The sample of 70 pregnant women at third trimester (38 to 40 weeks gestational age) was drawn by time frame quota sampling technique. Wilcoxon test was applied as an alternative of paired t-test due the abnormal data distribution. The p value of 0.01 was set. Mostly, the result of Johnson’s method showed estimation of birth weight was within normal category (66 out of 70 neonates/94,3%). Similarly, the majority of actual birth weight was within normal category (67 out of 70/95.7%).There was no significant difference between Johnson’s method and actual birth weight as proven by the p value = 0.066. It can be inferred that Johnson’s method was accurate to predict birth weight. Midwifery practitioners should use a standardized measuring instrument (tape measurement, baby weight scale) and perform a correct measurement technique to ensure the precise birth weight estimation.